Aspectos socioeconômicos, indicadores de qualidade do leite e pesquisa de linhagens toxigênicas de Staphylococcus em propriedades de agricultura familiar de Botucatu, SP - Lavor, Ubirajara Leoncy de [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Dairy farming on family farms is critical for survival and maintenance of the rural worker. Bovine mastitis negatively impacts milk production and presents risks to public health. This study evaluated the quality of the milk from the family farm in the region of Botucatu-SP, the difficulties faced by producers, the mastitis etiology, and sensitivity profile of pathogens against antimicrobials. Also evaluated the presence of enterotoxin producing genes in isolated staphylococcal strains. Also aimed the recommendation of actions to improve the production, seeking the quality of the milk. A Socioeconomic questionnaire was applied to producers and individual milk samples were collected from the set of brasses of each property and from cows diagnosed with mastitis by California Mastitis Test (CMT). It was evaluated the levels of fat, protein, lactose, dried extract and nonfat dry extract, the total bacterial count (TBC) and the somatic cell count (SCC). Twenty one (21) properties were analyzed where it was found that the average of the farmers was 59 years. Only five of them (23.8%) had completed high school or higher, and none (0%) counted on veterinary advice. As for their facilities of milking parlor, only four (19.0%) had stables with concreted floor and four (19.0%) used mechanical milking system. As to the handling, only one (4.8%) performed pre-dipping correctly, none (0%) performed post-dipping, two (9.5%) used disposable paper for milking and only two producers (9.5%) used the CMT with periodicity. On the other hand, 15 producers (71.4%) stated that they used anti mastitis for treating the cows. Regarding the animals, 239 cows (average = 11.4 animals / property) were evaluated. The clinical mastitis was detected in only two cows (<1%), whereas 86 animals showed milk positive to CMT (35.9% of subclinical mastitis). One hundred seventy-seven (177) milk samples were cultured, on 55 (31.1%) of them it was identified staphylococci, on ...

A atividade leiteira na agricultura familiar é fundamental para sobrevivência e manutenção do homem no campo. A mastite bovina impacta negativamente a produção leiteira e oferece riscos à saúde pública. O presente estudo avaliou a qualidade do leite proveniente da agricultura familiar na região de Botucatu-SP, as dificuldades enfrentadas pelos produtores, a etiologia das mastites, e o perfil de sensibilidade dos patógenos aos antimicrobianos. Avaliou-se também a presença de genes produtores de enterotoxinas em linhagens de Staphylococcus isoladas. Objetivou também a recomendação de ações para melhoria na produção, visando a qualidade do leite. Aplicou-se um questionário socioeconômico aos produtores e foram coletadas amostras individuais do leite do conjunto de latões de cada propriedade e de vacas diagnosticadas com mastite pelo California Mastitis Test (CMT). Avaliou-se os teores de gordura, proteína, lactose, extrato seco, extrato seco desengordurado, a contagem bacteriana total (CBT), e a contagem de células somáticas (CCS). Foram analisadas 21 propriedades onde constatou-se que a idade média dos produtores era de 59 anos. Apenas cinco deles (23,8%) tinham ensino médio completo ou superior, sendo que nenhum (0%) contava com assessoria veterinária. Quanto às instalações da sala de ordenha, apenas quatro (19,0%) possuíam estábulos com piso concretado e quatro (19,0%) utilizavam sistema de ordenha mecânica. Quanto ao manejo, apenas um (4,8%) realizava pré-dipping corretamente, nenhum (0%) realizava pós-dipping, dois (9,5%) utilizavam papel toalha descartável na ordenha e somente dois produtores (9,5%) utilizavam o CMT com periodicidade. Em contrapartida, 15 produtores (71,4%) revelaram terem utilizado antimastíticos para tratamento das vacas. Com relação aos animais, foram avaliadas 239 vacas (média = 11,4 animais/propriedade). A mastite clínica foi verificada em apenas duas vacas (<1%), enquanto que ...
Keywords: Agricultura familiar; Estafilococos; Enterotoxinas; Bovino de leite - Doenças; Leite - Qualidade; Mastite; Family farms